The future for creative writing - Harper, Graeme (Wiley-blackwell manifestos, 2014)
"This is a compelling look at the current state and future direction of creative writing by a preeminent scholar in the field. Explores the practice of creative writing, its place in the world, and its impact on individuals and communities Considers the process of creative writing as an art form and as a mode of communication Examines how new technology, notably the internet and cell phones, is changing the ways in which creative work is undertaken and produced Addresses such topics as writing as a cultural production, the education of a creative writer, the changing nature of communication, and different attitudes to empowerment" --